Examining the Effectiveness of Modular Instruction on Learners' Study Habits, Skills, and the International Bureau of Management Thailand in the Context of the COVID-19 Pandemic - Esmeralda, Angel (MID Publisher International, 2025)
Modular learning is a form of distance education that employs Self-Learning Modules based on the most essential learning competencies (MELCS) provided by DepEd. These modules contain sections on motivation and assessment, serving as a comprehensive guide for both teachers and students regarding their desired competencies. Modular learning is particularly relevant in the current situation. The threat posed by the Coronavirus or COVID-19 has significantly impacted not only the economic, tourism, and health sectors but has also adversely affected the global education system (Alvarez, 2020). This study aims to validate the modular instructions in relation to learners' study habits, skills, and attitudes in public schools during the COVID-19 pandemic, using a descriptive content analysis approach. The research focuses on selected fifth and sixth-grade students in the International Bureau of Management. Information was collected through surveys and interviews.